MEDAN MAKNA AKTIVITAS TANGAN BAHASA MELAYU PONTIANAK - Ida Herawati; Binar Kurniasari Febrianti (tuahtalino, 2016)
This study was to examine the meaning area of hand activities found in Malay language of Pontianak. The method used was descriptive method. The purpose of this study was to describe the existence of meaning area of hand activities which showed the meaning of inter lexemes-dealt structure. The result analysis showed that the lexeme grouping was based on the meaning components, which, in turn formed groups or sub area of specifics meanings. To determine the meaning components in which they were used to string such words which a meaning on each lexeme, the determination of formulation of its meta language was taken. In order to determine the meta language, it used guidance as a concept, such as hands or fingers, speed target, frequency, ways, and the purposes of the activities.